Exploring the Role of Schools in Early Prevention of Drug Abuse: A Systematic Review of Qualitative Studies in Elementary Education - Mumang, Andi Sri Wahyuni (International Journal of Technology and Education Research, 2026)
This study aims to examine the role of schools in early prevention of drug abuse through a systematic review of various qualitative studies in elementary school settings. The method employed was a qualitative narrative study approach, allowing for a deeper understanding of the meanings, experiences, and social dynamics involved in the implementation of school-based prevention programs. Data were collected from scientific articles published between 2020 and 2025 and analyzed using thematic analysis techniques. The results indicate that the role of schools in preventing drug abuse is reflected in three main dimensions: educational, preventive, and collaborative. Schools act as agents of value socialization through curriculum integration, character building, and the provision of a supportive social environment. Teachers and counselors play a strategic role as social role models and psychosocial support. However, this study also identified several challenges in implementation, including limited resources, inadequate training for educators, and suboptimal integration of the program into educational policy. Theoretically, these findings strengthen the relevance of social ecology and social learning approaches in understanding children's behavior related to the risk of substance abuse. This research has implications for the development of more contextual, participatory, and sustainable education policies and programs for early prevention efforts.